Making great lamps 50 illuminating projects, techniques and ideas - Morgenthal, Deborah 1950- (Lark Books, 1998)
Kyoto hanging lantern, tree branch floor lamp, wrought iron beaded lamp, paper mache floor lamp with two women, gourd sconce, leather-plaited gourd, Shaker-style table lamp, cheerleader-theme lamp, reader-themed lamp, fabric-covered PVC canister lamp, autumn leaf luminator, walnut floor lamp, copper gourd lamp, CD cabinet floor lamp, copper tubing lamp that bobs, corrugated lantern, free-form wire and handmade paper lamp, cypress lamp, fallen wood lamp with clock, lapidary lamp with basswood shade, bamboo lamp, geode night lamp, lamp made of plumbing supplies, kinetic lamp with string and knobs, paper globe swag lamp, Japanese washi lantern, Arts and crafts lamp.